Peran Kualitas Jasa dan Kepuasan Nasabah Terhadap Kesetiaan Nasabah Serta Minat Untuk Berpindah Bank - Clara, Catharina (Prosiding University Research Colloquium, 2018)
With so many banks in the banking system in Indonesia then certainly competition between banks is getting fierce. Each bank must inevitably create a superior quality of service compared to competitors so as to satisfy customers who ultimately result in customer loyalty or intention to switch banks considering the cost of bank switching (switching cost) is low. On the other hand banks must also comply with the guidelines of Bank Indonesia and the Financial Services Authority (FSA/ OJK). Based on this phenomenon then examined whether the perceived quality of the customer in this case is related to the bank customer satisfaction and loyalty as well as affect the desire or interest to switch banks. So the research problems are: 1) How does the quality of services and customer satisfaction bank and 2) What is the impact of customer satisfaction to customer loyalty and switch intention. This research is a survey conducted in Palembang to the people who are customers of banks in Palembang. Linear regression model used to measure the relationship between variables. To answer the first question, the independent variables of service quality (with 3 sub-variables: customer expectation, perceived quality, perceived value) regressed multiple with customer satisfaction. Meanwhile, to answer the second question, simple regression used to measure effect of customer satisfaction with customer loyalty and switch intention. The test results show that the reliability and validity of research instrument is already showing good reliability and validity. Similarly result with the classical assumption test. The influence of the quality of services measured using subvariable Customer Expectation, Perceived Quality and Perceived Value, to the customer satisfaction showed significance for the variable Perceived Quality. Customer satisfaction on customer loyalty significantly positive effect. Customer satisfaction against switch intention also significant but positive influence. Overall, these models haven?t predict the dependent variable properly.